Pengaruh Bauran Promosi dan Persepsi Harga terhadap Keputusan Pembelian pada Food Bowl Mangkok Makan Kota Tasikmalaya : Survei pada Konsumen Mangkok Makan di Kota Tasikmalaya - Sista Avrilyani; Arga Sutrisna; Barin Barlian3 (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
The purpose of this study was to determine the effect of Promotion Mix and Price Perception on Purchase Decisions at the Mangkok Makan Food Bowl in Tasikmalaya. This study uses a quantitative descriptive method. The sampling technique used in this study is a non-probability sampling technique by means of purposive sampling. Sources of primary data obtained from the distribution of questionnaires. The results show that Promotion Mix and Price Perception simultaneously have a significant effect on Purchase Decisions at the Mangkok Makan Food Bowl in Tasikmalaya, also Promotion Mix partially has a significant effect on Purchasing Decisions at the Mangkok Makan Food Bowl in Tasikmalaya and Partial Price Perception has not a significant effect on Purchase Decisions at the Mangkok Makan Food Bowl in Tasikmalaya.